HUBUNGAN SOCIAL SELF DISCLOSURE DENGAN GANGGUAN MENTAL EMOSIONAL PADA ORANG DENGAN HIV/AIDS DI KECAMATAN TUREN KABUPATEN MALANG - Galuh Kumalasari (CHMK NURSING SCIENTIFIC JOURNAL, 2019)
RELATIONSHIP OF SOCIAL SELF DISCLOSURE WITH MENTAL EMOTIONAL DISORDERS IN PEOPLE LIVING WITH HIV/AIDS (PLWHA) IN DISTRICT TUREN MALANG REGENCY Galuh Kumalasari Sekolah Tinggi Ilmu Kesehatan Kepanjen, Malang Email: galsyasss@gmail.com ABSTRACT Background: PLWHA (People Living with HIV/AIDS) not only experience physical impact but also an impact on mental emotional conditions. The problem is that PLWHA have a feeling of fear of being rejected and negative judgments related to their illness so that they tend to hide their status from the community (non social self disclosure). Ideally with someone doing self-disclosure in society (social self disclosure) will get a good source of support especially for a person's mental health condition. Objective: to analyze social self disclosure relationship with emotional mental disorders of PLWHA. Method: Used correlational analytic design with cross sectional approach. The number of respondents was 32 ODHA in Turen District, Malang Regency used total sampling. Results: The results of the analysis of the relationship between social self disclosure and emotional mental disorder found that there were PLWHA who did not experience mental emotional disorders who did social self disclosure were 13 PLWHA (40.6%). Whereas among PLWHA who experienced mental emotional disturbances who did social self disclosure to the community were 5 PLWHA (15.6%). The results of statistical tests obtained p = 0.014, it can be concluded that there is a difference in the proportion of social self disclosure between PLWHA who experience and do not experience mental emotional disorders (there is a significant relationship between social self disclosure with mental emotional disorders). Conclusion: This study proves that there is a relationship between social self disclosure and mental emotional disorders in PLWHA in Turen District, Malang Regency. PLWHA who do social self disclosure to the community well have a greater chance of not experiencing emotional mental disorders. Keywords: Social Self Disclosure, Emotional Mental Disorders